Nanocompósito de óxido de grafeno e nanopartículas metálicas para espectroscopia raman amplificada por superfície (SERS) - Vianna, Pilar Gregory (2017)
Light interaction with the electronic cloud of metallic nanoparticles at frequencies that are resonant with the natural oscillation frequency of the cloud is known to excite localized surface plasmons. This phenomenon is widely used to enhance the Raman signal, known to have small cross sections. The technique, known as surface-enhanced Raman spectroscopy (SERS), enables the detection of chemical and biological species with high sensitivity. However, charge transfer mechanisms, adsorption/desorption and changes in the substrate morphology induce temporal instability of the SERS signal, known as blinking, which is an obstacle to the precise detection of the molecules under analysis. In this work, we, therefore, propose a SERS substrate composed of graphene oxide and gold nanorods, capable of suppressing the temporal fluctuations in the intensity of the spectrum. Temporal stability is statistically determined by the coefficient of variation of the integrated spectra, from which it is verified that, with the addition of graphene oxide, the nanocomposite is five times more stable than with gold nanorods only. The stability improvement is attributed to the removal of the nanorods’ surfactant from plasmonic hot spots due to graphene oxide-surfactant interaction. Thus, the nanocomposite is used as a reliable SERS substrate in the detection of Rhodamine 640. The analysis indicates a Rodamine detection that is four times more stable with the nanocomposite, than without graphene oxide. The nanocomposite is then used for the coating of the inner surface of microcapillaries. Graphene oxide and gold nanorod suspensions are subsequently used to fill the capillaries, with a drying step for the evaporation of solvents in between each filling stage. The continuous coating of the capillary fibers with the nanocomposite is verified by Raman spectroscopy, and Rhodamine 640 is used as a probe molecule, this time inside the capillaries, for SERS analysis. The microcapillaries allow for the use of small amounts of sample, and smaller concentrations than those detected with other reported optofluidic substrates are measured.